Determination of Attitudes and Intentions to Adopt Mobile Banking of Sharia Banking Customers in Greater Bandung: Technology Acceptance Model and Religiosity Approach - Nur'aeni, Nur'aeni; Huda, Badriyatul; Wazdi, Adi Indradi; Setiawan, Setiawan (Fakultas Ekonomi dan Bisnis Islam, 2025)
This study identifies key variables, such as perceived usefulness, ease of use, trust, and security, that influence attitudes toward mobile banking and their impact on adoption intentions. TAM has been widely used in previous studies, but few have examined how religiosity can moderate the relationship between these factors in the context of Islamic banking. By considering the Islamic values that underlie financial decision-making by Islamic customers, this study is expected to provide a more holistic understanding of technology adoption in Islamic banking. A survey was conducted with 209 respondents in Greater Bandung, and the data were analyzed using SEM-PLS. The results showed that perceived usefulness and ease of use significantly influenced attitudes toward mobile banking, while trust, security, and religiosity did not. However, religiosity proved to have a highly significant effect on adoption intentions, while attitude had no effect. These findings confirm that the adoption of Islamic mobile banking is more influenced by religiosity than by users' attitudes toward technology